Interpersonal Meaning Analysis in the Tale’s Story of Sabai Nan Aluih - Uswar, Yenita; Andriani, Nova (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2020)
Systemic Functional Linguistics (SFL) is a study of language which views language as two characteristics, systemic and functional. With using SFL, the researchers try to analyze the tale’s story of Sabai Nan Aluih. The research aim is to identify the interpersonal meaning realized in that story and to reveal the speech function of language use in that story. The research design of this analysis is descriptive qualitative research. The object of this research is the interpersonal meaning analysis of clauses as exchange in the tale of Sabai Nan Aluih. The data of this research is the clauses as exchange in the story of Sabai Nan Aluih. The source of data which is used in this research is the documentation of the data research paper. The researchers use document analysis from the story of Sabai Nan Aluih as collecting data. The data is analyzed by using description method. In the interpersonal analysis, declarative mood dominates almost the story, it is about 91 %. And, the data analysis of speech function is found in the story of Sabai Nan Aluih, statement, question and command, in where statement is domination from the story about 94%. Thus, it is important that the using of interpersonal meaning and the speech function of the story of Sabai Nana Aluih is as information